Effects of Neonatal Enzyme Replacement Therapy and Simvastatin Treatment on Cervical Spine Disease in Mucopolysaccharidosis I Dogs. (December 2014) - Chiaro, Joseph A; O'Donnell, Patricia; Shore, Eileen M; Malhotra, Neil R; Ponder, Katherine P; Haskins, Mark E; Smith, Lachlan J
ABSTRACT Mucopolysaccharidosis I (MPS I) is a lysosomal storage disease characterized by deficient α‐L‐iduronidase activity, leading to the accumulation of poorly degraded glycosaminoglycans (GAGs). Children with MPS I exhibit high incidence of spine disease, including accelerated disc degeneration and vertebral dysplasia, which in turn lead to spinal cord compression and kyphoscoliosis. In this study we investigated the efficacy of neonatal enzyme replacement therapy (ERT), alone or in combination with oral simvastatin (ERT + SIM) for attenuating cervical spine disease progression in MPS I, using a canine model. Four groups were studied: normal controls; MPS I untreated; MPS I ERT‐treated; and MPS I ERT + SIM–treated. Animals were euthanized at age 1 year. Intervertebral disc condition and spinal cord compression were evaluated from magnetic resonance imaging (MRI) images and plain radiographs, vertebral bone condition and odontoid hypoplasia were evaluated using micro–computed tomography (µCT), and epiphyseal cartilage to bone conversion was evaluated histologically. Untreated MPS I animals exhibited more advanced disc degeneration and more severe spinal cord compression than normal animals. Both treatment groups resulted in partial preservation of disc condition and cord compression, with ERT + SIM not significantly better than ERT alone. Untreated MPS I animals had significantly lower vertebral trabecular bone volume and mineral density, whereas ERT treatment resulted in partial preservation of these properties. ERT + SIM treatment demonstrated similar, but not greater, efficacy. Both treatment groups partially normalized endochondral ossification in the vertebral epiphyses (as indicated by absence of persistent growth plate cartilage), and odontoid process size and morphology. These results indicate that ERT begun from a very early age attenuates the severity of cervical spine disease in MPS I, particularly for the vertebral bone and odontoid process, and that additional treatment with simvastatin does not provide a significant additional benefit over ERT alone. © 2014 American Society for Bone and Mineral Research.